A First Large-Scale Monitorization Report Highlighting Exotic Pets As An Emergent Reservoir of MultiDrug Resistant Bacteria (Toulouse, France). (March 2022) - Cardoso, S.; Loc'h, A. Le; Craveiro, H.; Anastácio, S.; Sousa, S.; Silveira, E.
Abstract : Purpose: Antibacterial resistance is one of the greatest hazard of worldwide public heath. This study aimed to assess the prevalence of MutiDrug resistant (MDR) bacteria between 2017 and 2019 in both Gram-negative and positive bacteria, from exotic pets originating from France. Methods & Materials: Isolates (n=2050) were identified using MALDI-TOF mass spectrometry. Antimicrobial susceptibility testing was assayed by disk diffusion methods to 11 antibiotic classes following CA-SFMVET and EUCAST guidelines. Statistical analyses were performed using GraphPad Prism® (version 8.4.2.) and differences were considered relevant if p <0.05. AMR rates were analyzed (p<0, 0001) to evaluate the resistance profile among the three years. Results: Isolates showed high resistance levels and particular MDR phenotypes to different antibiotic classes: E. faecalis (n=79/125; 63, 2%), Streptococcus spp. (n=68/249; 27, 3%), E.coli (n=52/155; 33, 5%), Staphylococcus spp. (n=51/212; 24%), Enterobacter spp. (n=39/131;29, 7%), Klebsiella spp. (n=32/111; 28, 8%), S.xylosus (n=28/143; 19, 5%), S.epidermidis (n=25/47; 53%), S.aureus (n=23/122; 18, 8%), Enterococcus spp. (n=23/58; 39, 6%), Pasteurella spp. (n=14/226; 6, 2%), Serratia spp. (n=9/66; 13, 6%), Lactococcus spp. (n=8/10; 80%), Citrobacter spp.and Gemella spp. (n=7/23; 7/38;30, 4%, 18, 4% respectively), Proteus spp., Raoultella spp., Salmonella spp. and Mannheimia spp. (n=3/65; 3/10; 3/6; 3/16; 4, 6%, 30%, 50%, 18, 7%, respectively), Vagonococcus fluvialis (n=2/3; 66, 6%), Rahnella spp., Actinobacillus spp. and Chelonobacter oris (n=1/4; 1/6; 1/2; 25%, 16, 6%, 50%, respectively). It should be noted that some of MDR bacteria are simultaneously resistant to all antibiotics tested in this study: Enterococcus faecalis (n=47/49; 95, 0%), E.coli (n=19/52; 36, 5%), Klebsiella spp. (n=12/32; 37, 5%), S.epidermidis (n=7/25; 28%), Streptococcus spp. (n=6/68; 8, 8%), Enterococcus spp. (n=6/23; 26%), Staphylococcus spp. (n=4/51; 7, 8%), Lactococcus spp. (n=4/8; 50%), Citrobacter spp. (n=3/7; 42, 8%), Raoultella spp. (n=2/3; 66, 6%), Serratia spp, (n= 1/9; 11, 1%), Pasteurella spp (n=1/14; 7, 1%) and S. xylosus (n=1/28; 3, 5%). Conclusion: These results highlight exotic pets as an emergent reservoir of MDR bacteria, with focus on E. faecalis . Monitoring antimicrobial-resistance including clonal lineages identification in all animal species amongst restrictive antibiotic use policies, improvement measures and preliminary interventions are urgently required. This is the first report of a large-scale monitoring antimicrobial resistance in exotic pets bringing new insights to the current status of antimicrobial resistance.